Novel joint iterative channel estimation and space-frequency decoding algorithm for SFBC-OFDM systems - ZHOU Peng; ZHAO Chun-ming; YANG Yi-jin; XU Wei (Tongxin xuebao)
A novel joint iterative channel estimation and space-frequency decoding algorithm was proposed for SFBC-OFDM systems.At first,a new channel estimation algorithm based on time-frequency transforms（TFT） was de-veloped to improve the performance of the initial channel estimator,and then,by exploiting the channel estimated values and the decoded symbols,the joint iterative channel estimation and space-frequency decoding algorithm was advanced.Analyses and simulation results show that the novel joint iterative algorithm improves performance remarkably for the quasi-static,fast time-varying and correlated channels.